A study on a 210Pbex accumulation-decay model for dating moraine soils to trace glacier retreat time. (February 2020) - Chen, Jiacun; Zhang, Xinbao; Navas, Ana; Wen, Anbang; Wang, Xiaoxiao; Zhang, Runchuan
Abstract: This paper reports work exploring the potential for using the natural fallout radionuclide 210 Pbex to date moraine soils for tracing glacier retreat. Based on the physical processes of 210 Pbex deposition, decay and losses due to runoff, a 210 Pbex accumulation-decay model ( A n = I [ 1 − λ n + 1 1 − λ − b ( c n + 1 − λ n + 1 ) c − λ ] ) was developed, where A n = 210 Pbex inventory (Bq·m −2 ); I = annual inventory of 210 Pbex deposition (Bq·m −2 ); λ = 210 Pb decay coefficient (0.969); n = time span (years); b and c = 210 Pbex loss coefficients for the runoff pathway. Furthermore, 137 Cs was used to identify the ages of the study sites and to support the 210 Pbex model results. The model was validated with data obtained from the Hailuogou Glacier Valley, Mt. Gongga, in 2016, where nine glacier retreat moraine points were recorded from 1910 to 1990 along a retreat length of 1750 m in the valley. 210 Pbex inventories increased from 3, 669.6 ± 218.5 Bq·m −2 at the site where the glacier retreated in 1990 to 10, 718.9 ± 167.4 Bq·m −2 in 1910. The coefficients of b = 0.6006 and c = 0.9764 were derived from the 210 Pbex inventories at the nine sites with recorded glacier retreat times that were marked with special stone and terrain features. The goodness-of-fit (GOF) for the model predictions of glacier retreat times is 65.5%. The results obtained confirm that the fallout radionuclide 210 Pbex has potential for dating moraine soils in other cryosphere regions throughout the world as well as for other types of records forming sedimentary landform sequences such as soils on debris flows and alluvial fans. Highlights: For the first time a 210 Pbex accumulation-decay model is developed on moraines. The 210 Pbex physically-based model considers the effect of water erosion. Runoff coefficients should be established for each study area. The model is suitable for dating moraine soils over the past 100 years.